Polar Bear Maternal Den Habitat in the Arctic National Wildlife Refuge, Alaska - Durner, George M.; Amstrup, Steven C.; Ambrosius, Ken J. (ARCTIC, 2009)
Polar bears (Ursus maritimus) give birth during mid-winter in dens of ice and snow. Denning polar bears subjected to human disturbances may abandon dens before their altricial young can survive the rigors of the Arctic winter. Because the Arctic coastal plain of Alaska is an area of high petroleum potential and contains existing and planned oil field developments, the distribution of polar bear dens on the plain is of interest to land managers. Therefore, as part of a study of denning habitats along the entire Arctic coast of Alaska, we examined high-resolution aerial photographs (n = 1655) of the 7994 km2 coastal plain included in the Arctic National Wildlife Refuge (ANWR) and mapped 3621 km of bank habitat suitable for denning by polar bears. Such habitats were distributed uniformly and comprised 0.29% (23.2 km2) of the coastal plain between the Canning River and the Canadian border. Ground-truth sampling suggested that we had correctly identified 91.5% of bank denning habitats on the ANWR coastal plain. Knowledge of the distribution of these habitats will help facilitate informed management of human activities and minimize disruption of polar bears in maternal dens. Les ours polaires (Ursus maritimus) mettent bas au beau milieu de l’hiver dans des tanières de glace et de neige. Les ours polaires des tanières qui sont la cible de dérangements occasionnés par l’être humain peuvent abandonner leur tanière avant que leurs petits ne soient prêts à survivre les rigueurs de l’hiver de l’Arctique. Puisque la plaine côtière arctique de l’Alaska renferme de grandes possibilités sur le plan pétrolier et comprend des champs pétrolifères mis en valeur ou dont la mise en valeur est planifiée, la répartition des tanières d’ours polaires sur la plaine revêt de l’intérêt chez les gestionnaires des terres. Par conséquent, dans le cadre d’une étude portant sur les habitats des tanières tout le long de la côte arctique de l’Alaska, on a examiné des photographies aériennes de haute résolution (n = 1655) portant sur une ...